Stylistic Analysis of Distorted Harmony’s Songs Lyric on Chain Reaction Album - Sofyansyah, Aldino Ade; Rahayu, Famala Eka Sanhadi; A, Alamsyah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
ABSTRACT Songwriters or poet have their styles in writing their literary works, such as violating the rules or using parallelism to create aesthetic value or emphasize a certain message. One of them is morphological repetition. This study intends to find out the morphological repetitions and their contributions to the meaning of Distorted Harmony song lyrics. To conduct this study, the theory of Leech, Heinrich F. Plett, and Arthur Quinn of morphological repetition and qualitative methods were used in this study. The result of this study showed that there were 8 types of morphological repetition such as polyptoton, antanaclasis, isolcolon, repititio, epizeuxis, diacope, anaphora, and epistrophe. According to the research finding, anaphora was the most frequently used in the Distorted Harmony song lyrics. The conclusion is that Distorted Harmony used morphological repetition in their song lyrics to emphasize the message they convey.ABSTRAK Penulis lagu atau penyair memiliki gaya tersendiri dalam menulis karya sastranya, seperti melanggar aturan atau menggunakan paralelisme untuk menciptakan nilai estetika atau menekankan pesan tertentu. Salah satunya adalah repetisi morfologis. Penelitian ini bertujuan untuk mengetahui repetisi morfologis dan kontribusinya terhadap makna lirik lagu Distorted Harmony. Untuk melakukan penelitian ini, teori dari Leech, Heinrich F. Plett, dan Arthur Quinn tentang pengulangan morfologi dan metode kualitatif digunakan dalam penelitian ini. Hasil penelitian menunjukkan bahwa terdapat 8 jenis repetisi morfologis yaitu poliptoton, antanaclasis, isolcolon, repititio, epizeuxis, diacope, anaphora, dan episthrope. Menurut hasil penelitian, anafora paling sering digunakan dalam lirik lagu Distorted Harmony. Kesimpulannya adalah Distorted Harmony menggunakan repetisi morfologis dalam lirik lagu mereka untuk menekankan pijatan yang mereka sampaikan.